1988
DOI: 10.3109/07357908809077025
|View full text |Cite
|
Sign up to set email alerts
|

Digital Dermatoglyphics in Mammary Cancer

Abstract: Fingerprints from 200 women with histologically proven breast cancer (case group) were compared to fingerprints from 138 women with no history of any malignant disease (control group). Of the patterns analyzed, four were significantly associated with breast cancer: accidentals, transitionals, angled ulnar loops, and horizontal ulnar loops. A fifth print, the angled radial loop, was found to be of borderline importance as an independent predictor of breast cancer. Of 200 patients in the case group, 27 had one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The finger and palmar print patterns have already been studied with respect to various genetic diseases like the Down's syndrome and Klinefelter syndrome [4,5]. The prints can thus represent a noninvasive anatomical marker of breast cancer risk [4][5][6]. An effort in this regard has been made to devise a screening program for breast cancer using fingerprints or dermatoglyphic study in order to select the high-risk group for surveillance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finger and palmar print patterns have already been studied with respect to various genetic diseases like the Down's syndrome and Klinefelter syndrome [4,5]. The prints can thus represent a noninvasive anatomical marker of breast cancer risk [4][5][6]. An effort in this regard has been made to devise a screening program for breast cancer using fingerprints or dermatoglyphic study in order to select the high-risk group for surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…have been extensively studied and identified as genetic links [1][2][3]. Evidence is available suggesting that a family history of breast cancer might be associated with a specific fingerprint pattern [4][5][6][7][8]. Finger print determination is genetic but has been reported to be affected by the environmental factors in the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Natekar et al 2006 (9) also concluded that females whose fingerprint patterns had more than six loops, had 46 times higher risk of developing breast cancer when compared to controls. Bierman et al 1988 (18) and Sridevi 2010 (19) observed that ulnar loops were significantly associated with breast cancer. On the other hand, Fulari et al 2012 (17) found a lower percentage of ulnar loops in breast cancer patients compared to controls, which is consistent with the results obtained by Sukre et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning specifically the Caucasian population is not present in the Huang manuscript for comparison with our population. Bierman et al [1988] noted that accidental, transitionals, angled ulnar loops, and horizontal ulnar loops were significantly associated with breast cancer. The authors did not find an association with multiple whorls and breast cancer as we have and their data for this comparison are not included in their manuscript.…”
Section: Discussionmentioning
confidence: 99%